“All sorts of colours of emotions”: Ambulance call-handlers’ perceptions of the barriers to CPR in out-of-hospital cardiac arrest - Barbara Farquharson; Marie Johnston; Rosaleen O’Brien; Gareth Clegg (Resuscitation Plus)
Aim: To explore call-handlers’ perceptions of the main barriers to achieving CPR during emergency calls to the ambulance service. Methods: Thirty purposively sampled call-handlers, working in seven UK ambulance dispatch centres, participated in semi-structured qualitative interviews designed to explore their experiences of providing CPR instructions and their perceptions of the most common barriers to initiation of CPR. Results: Participants (20F 9 M 1non-binary), aged 21–57 years, with varied length of experience (6mths −25 yrs), self-reported confidence (3–10/10), experience of NHS Pathways and MPDS, described providing CPR calls typically once per shift, with most call-handlers reporting barriers to CPR in most calls.The barriers to initiating CPR most commonly identified by call-handlers were the strong emotions experienced by callers; physical issues relating to the caller, patient and situation; uncertainty about whether CPR was required, particularly uncertainty about breathing and caller concerns about doing harm.Participants described many overlapping issues, making each call a unique challenge. They also provided insights into the complexities of ambiguous situations such as those encountered by carers and care-homes, DNACPR issues, as well as facilitating factors. Conclusion: Call-handlers identified barriers to CPR that echo those identified via other study methods plus provide additional insights into areas not readily addressed by current protocols. Call-handlers’ perspectives may be helpful in identifying priority areas for protocol refinement and ways to improve the efficacy of CPR instructions.